Thermal-Fluid Transport Phenomena of a Strongly-Heated Gas Flow in Parallel Tube Rotation - Shuichi Torii (International Journal of Rotating Machinery, 1998)
A numerical analysis is performed to study thermal transport phenomena in gas flow through a strongly heated tube whose axis is in parallel with the rotational axis. The velocity and temperature fields prevail when fluid flows in a rotating tube with uniform heat flux on the tube wall. The two-equation k-ω turbulence and t2¯-εt heat transfer models are employed to determine turbulent viscosity and eddy diffusivity for heat, respectively. The governing boundary-layer equations are discritized by means of a control volume finitedifference techniques. It is found that the Coriolis and centrifugal (or centripetal) forces cause fluid flow and heat transfer performance in the parallel-rotation system to be drastically different from those in the stationary case. Consequently, even if a tube rotating around a parallel axis is heated with high heat flux whose level causes a laminarizing flow in the stationary tube case, both the turbulent kinetic energy and the temperature variance remain over the pipe cross section, resulting in the suppression of an attenuation in heat transfer performance. In other words, an increase in tube rotation suppresses laminarization of gas flow.